Immune‐monitoring in Kawasaki disease patients treated with infliximab and intravenous immunoglobulin. (24th October 2013) - Burns, J. C.; Song, Y.; Bujold, M.; Shimizu, C.; Kanegaye, J. T.; Tremoulet, A. H.; Franco, A.
Summary: The expansion of regulatory T cells (Treg ) controls inflammation in children with acute Kawasaki disease (KD). Blockade of tumour necrosis factor (TNF)‐α is an emerging therapy for KD patients with refractory inflammation, but there is concern that this therapy could impede the host immune regulation. To define the effect of TNF‐α blockade, we conducted ex‐vivo immune‐monitoring in KD subjects who participated in a randomized, double‐blind, placebo‐controlled clinical trial of the addition of infliximab to standard intravenous immunoglobulin (IVIG) therapy. We enumerated circulating myeloid and plasmocytoid dendritic cells (DC), regulatory T cells (Treg ) and memory T cells (Tmem ) in 14 consecutive, unselected KD patients (seven treated with IVIG, seven with IVIG + infliximab) at three time‐points: (i) acute phase prior to treatment, (ii) subacute phase and (iii) convalescent phase. Myeloid DC (mDC), but not plasmacytoid DC (pDC), were numerous in the peripheral blood in acute KD subjects and decreased in the subacute phase in both IVIG − and IVIG + infliximab‐treated groups. The co‐stimulatory molecule for antigen presentation to T cells and CD86 decreased in mDC from acute to subacute time‐points in both treatment groups, but not in the single patient who developed coronary artery aneurysms. We also defined tolerogenic mDC that expand in the subacute phase of KD not impaired by infliximab treatment. Treg and Tmem expanded after treatment with no significant differences between the two groups. Treatment of KD patients with infliximab does not adversely affect generation of tolerogenic mDC or the development of T cell regulation and memory.